Determination of Optimal Portfolio by Calculating Transaction Costs using Genetic Algorithms on the Jakarta Islamic Index - Fadhila, Sinta Oktavia Nur; Abadi, Agus Maman; Setiawan, Ezra Putranda (Universitas Muhammadiyah Mataram, 2024)
The optimal portfolio is a portfolio that can provide maximum returns at the same level of risk. In investing, the term